Effects of excavation sequence and heading distance on settlement in New Austrian tunneling method - Sohaei, Houman (2012)
The shallow underground excavation may leads to ground movements and surface settlement which may cause damage to structures. Several tunnel excavation methods had been developed during the last decades to minimize the effects of the tunnel construction on the surface settlement. The Karaj Metro tunnel (KMT) had been constructed in accordance with the principles of the New Austrian Tunneling Method (NATM). This method had been used widely to construct large diameter tunnels mainly due to its flexibility to adapt different ground conditions. Tunnel designs by NATM are generally based on empirical and numerical methods and construction process may be changed according to the observed response of the ground. Induced displacements are empirically controlled by adjusting the excavation rate, distance between tunnel face and support, partial heading excavation and closure of invert. This research is aimed at determining the effects of the excavation sequence and heading distance on the surface and subsurface settlement by carrying out two and three-dimensional Finite Element Modelling (FEM). Initially, the FEM is carried out to simulate step by step excavation sequence of KMT which had been constructed in soft soils by NATM method. The settlements obtained from monitoring of KMT had been used to validate the modelling work. The results show that the settlement varies with different excavation sequence and heading distance in NATM. The Side Galleries (SG) excavation model produced the lowest transverse and longitudinal surface settlements compared to KMT excavation model and other excavation sequences. The tunnel heading distance had more effect on both the transverse and longitudinal settlements for the KMT excavation model compared to SG model. Hence, the SG excavation model with heading distance of 2 m is recommended in the construction of KMT using NATM based on the minimum settlement occurring during excavation.